Health Locus of Control and Perceived Levels of Depression, Anxiety, Stress Among Pakistani Female Breast Cancer Patient - Naz, Rubina; Ambreen , Saima (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore how psychological strengths of Health Locus of control influence to psychological distresses (depression, anxiety, stress) in breast cancer female patients. Study Design: Cross sectional study. Place and Duration of Study: Oncology Department, Shifa International Hospital, Islamabad Pakistan, from Mar 2021 to Feb 2022. Methodology: A non- probability sampling technique (purposive sampling) was used. A total sample of n = 115 breast cancer patients whose age range was from 28- 89 years. A biographical sheet that contains personal and disease information of patient, along with two indigenously adapted standardized scales were used: Multidimensional Health Locus of Control Form- C (Wallston, Stein, & Smith, 1994), and DASS-21 (Lovibond & Lovibond, 1995). To assess the construct under observation in current study. Results: Findings suggested that Internal Health Locus of Control (IHLoC) and Doctors HLoC (DHLoC) are significantly and negatively correlated with DASS (Depression, Anxiety, and Stress) p<0.05, p<0.001 respectively. Conversely, the MHLoC subscale Chance (CHLoC) and Others HLoC are positively correlated with DASS with (p<0.05, p>0.05 respectively). The statistical regression analysis revealed Internal Health Locus of Control negatively influence to depression anxiety and stress (R²= 0.06, p<.05; F (1, 113) = 6.75, p<0.05), same on doctor HLoC, while all external dimension showed positive significant influences on outcome variable DASS (Depression, Anxiety, Stress). Conclusion: Strength factor of internal health locus of control enables breast cancer patient to fight against psychological distresses. Psychologists, counselors/ therapists who are serving in oncology department, health care personnel’s recommendations are suggested.